Tantangan Kepribadian Remaja di Era Media Sosial - Fathinah, Rafa Azzahra (Lembaga Yasin AlSys, 2024)
The message is that technological developments in the 21st century also create a new order of life for modern humans. Technological developments and globalization can directly or indirectly influence the moral development of teenagers in the millennial era. The purpose of this writing is to find out the personality challenges of teenagers in the era of social media. This article uses a literature study method, by collecting sources of information that are appropriate to the focus being discussed, then the information is arranged in the form of a description. The use of social media also influences the behavior and well-being of teenagers, as well as improving or strengthening each person's reputation and trust. In addition, social media can be used for effective information dissemination and developing social skills, but negative impacts tend to occur, such as the spread of false or dangerous information. , which can threaten the order of a young person's personal life. From this impact, it is important for families, communities and stakeholders to understand how to use social media well and integrate teenagers' use of social media.